Educational data mining: overview and research trends - Stumbrienė, Dovilė; Jakaitienė, Audronė (Lietuvos matematikos rinkinys, 2015)
The article presents a systematic literature review about the most commonly used data sources and data mining methods in education. International database Web of Science was selected. Excluding short conference proceedings and articles without empirical data, 14 papers were analyzed in detail. It was obtained that the most explored databases of learners consisted of subjects evaluation results together with contextual information. Classification methods were the most commonly used; to a lesser extent regression analysis and clustering. An educational data mining research overview in Lithuania ends the article.
Keywords: data mining; education; clustering; classification; regression